2016
DOI: 10.3892/ol.2016.4316
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-133b sensitizes non-small cell lung cancer cells to irradiation through the inhibition of glycolysis

Abstract: Abstract. Non-small cell lung cancer (NSCLC) accounts for 85% of all types of lung cancer and is the leading cause of world-wide cancer-associated mortalities. Radiation therapy has long been regarded as a fundamental therapeutic treatment strategy for NSCLC. However, alternative therapies for NSCLC remain insufficient, with the majority of cancers developing a high incidence of radioresistance. MicroRNAs (miRNAs/miRs) are endogenous oligonucleotide RNAs that serve an important role in carcinogenesis and tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 22 publications
0
30
1
Order By: Relevance
“…Previous studies revealed that a growing number of miRNAs are involved in the radiosensitivity of cancers including NSCLC . In lung cancer cells, overexpression of miR‐133b can sensitize radioresistant lung cancer cells by inhibiting pyruvate kinase isoform M2 (PKM2)‐mediated glycolysis . Downregulation of miR‐21 can reverse the radiosensitivity of NSCLC cells via targeting tumor suppressor PTEN .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that a growing number of miRNAs are involved in the radiosensitivity of cancers including NSCLC . In lung cancer cells, overexpression of miR‐133b can sensitize radioresistant lung cancer cells by inhibiting pyruvate kinase isoform M2 (PKM2)‐mediated glycolysis . Downregulation of miR‐21 can reverse the radiosensitivity of NSCLC cells via targeting tumor suppressor PTEN .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu et al found that miR-133b overexpression sensitized radioresistant lung cancer cells by inhibiting pyruvate kinase isoform M2 (PKM2)-mediated glycolysis [28]. Liu et al reported that miR-21 downregulation inhibited cell growth, metastasis and reversed chemo- and radio-sensitivity of NSCLC cells by targeting tumor suppressor PTEN [29].…”
Section: Discussionmentioning
confidence: 99%
“… 33 miR-133b was also verified to correlate with radiation therapy in lung cancer cells, and it was low expressed in radioresistant lung cancer cells. 72 Elevating expression of miR-133b contributed to radioresistant lung cancer cells being resensitive, and the relevant pathway was involved in pyruvate kinase isoform M2-mediated glycolysis. 72 In addition, Wu et al.…”
Section: Main Textmentioning
confidence: 99%
“… 72 Elevating expression of miR-133b contributed to radioresistant lung cancer cells being resensitive, and the relevant pathway was involved in pyruvate kinase isoform M2-mediated glycolysis. 72 In addition, Wu et al. 73 demonstrated that cationic lipids combined with pre-miR-133b significantly elevated the level of mature miR-133b in the lung cancer A549 cell and in the mouse model.…”
Section: Main Textmentioning
confidence: 99%